2000
DOI: 10.1074/jbc.m004248200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Balance of One-carbon Metabolism inSaccharomyces cerevisiae

Abstract: One-carbon metabolism in yeast is an essential process that relies on at least one of three one-carbon donor molecules: serine, glycine, or formate. By a combination of genetics and biochemistry we have shown how cells regulate the balance of one-carbon flow between the donors by regulating cytoplasmic serine hydroxymethyltransferase activity in a side reaction occurring in the presence of excess glycine. This control governs the level of 5,10-methylene tetrahydrofolate (5,10-CH 2 -H 4 folate) in the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 28 publications
3
100
0
2
Order By: Relevance
“…Piper et al (16) demonstrated that this response is mediated by a decrease in cytoplasmic levels of 5,10-CH 2 -H 4 folate. Given the central role of H 4 folate intermediates in one-carbon metabolism, it was proposed that this novel "glycine response" might represent a more general one-carbon metabolic transcriptional control system (regulon).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Piper et al (16) demonstrated that this response is mediated by a decrease in cytoplasmic levels of 5,10-CH 2 -H 4 folate. Given the central role of H 4 folate intermediates in one-carbon metabolism, it was proposed that this novel "glycine response" might represent a more general one-carbon metabolic transcriptional control system (regulon).…”
Section: Resultsmentioning
confidence: 99%
“…GCV2 expression is decreased, but still glycine-responsive, in a met13 strain, which lacks the main methylenetetrahydrofolate reductase activity of the cell (16). The effect of this mutation is thus to reduce synthesis of 5-CH 3 -H 4 folate from 5,10-CH 2 -H 4 folate.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…Flux through these reactions is generally oxidative in the mitochondria and reductive in the cytoplasm; however, C1 metabolic pathways are under considerable regulatory control and can be adapted to specific genetic backgrounds and growth conditions (Kastanos et al 1997;Piper et al 2000). Two groups have independently shown that C1 enzymes are controlled dynamically by glycine at the transcriptional level.…”
mentioning
confidence: 99%
“…In photosynthetic tissues of plants, the GCC consumes large amounts of glycine produced during photorespiration (18), but the activity is still essential in Arabidopsis even under non-photorespiratory conditions (21). In Saccharomyces cerevisiae, mutants lacking any of the GCCspecific subunits can grow on minimal medium but cannot use glycine as a nitrogen source (20).…”
mentioning
confidence: 99%